2021
DOI: 10.3390/v13071335
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Pterostilbene Inhibit SARS-CoV-2 Replication in Air–Liquid Interface Cultured Human Primary Bronchial Epithelial Cells

Abstract: The current COVID-19 pandemic is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and has an enormous impact on human health and economy. In search for therapeutic options, researchers have proposed resveratrol, a food supplement with known antiviral, anti-inflammatory, and antioxidant properties as an advantageous antiviral therapy for SARS-CoV-2 infection. Here, we provide evidence that both resveratrol and its metabolically more stable structural analog, pterostilbene, exhibit potent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“…Besides their established antioxidant and anti-inflammatory properties, several studies demonstrated their significant protection against viruses and several pathogens, including the Epstein–Barr and herpes simplex viruses [ 5 , 6 , 7 ]. We have already demonstrated the ability of resveratrol in inhibiting the replication of influenza A virus [ 8 ], and recent research in this field demonstrates that various types of polyphenols, such as resveratrol and pterostilbene, are promising antiviral compounds to inhibit SARS-CoV-2 infection [ 9 ]; indeed, other research aligns perfectly with these results [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 78%
“…Besides their established antioxidant and anti-inflammatory properties, several studies demonstrated their significant protection against viruses and several pathogens, including the Epstein–Barr and herpes simplex viruses [ 5 , 6 , 7 ]. We have already demonstrated the ability of resveratrol in inhibiting the replication of influenza A virus [ 8 ], and recent research in this field demonstrates that various types of polyphenols, such as resveratrol and pterostilbene, are promising antiviral compounds to inhibit SARS-CoV-2 infection [ 9 ]; indeed, other research aligns perfectly with these results [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 78%
“…To investigate the feasibility of the Nluc reporter viruses for antivirals screening, we selected two drugs that were reported to have a negative effect on CoVs replication, namely lycorine [ 43 ] and resveratrol [ 44 ]. To exclude cytotoxic side effects, cell viability upon lycorine treatment was determined.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to previously reported real-time cell analysis (RTCA) systems for high-throughput screening of antivirals [ 50 ], the Nluc reporter virus possesses the obvious advantages with more simpler operation features. A recent study showed that resveratrol inhibits SARS-CoV-2 infection in Vero E6 cells and air–liquid interface cultured human primary bronchial epithelial cells (PBEC) as opposed to human lung epithelial cells (Calu-3), suggesting inherent differences between these different cell line models [ 44 ]. However, PDCoV possesses unusual wide cell tropisms.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that resveratrol targeted caspase 3 in Vero E6 cells, as well as the nucleocapsid protein of MERS CoV. A concentration ranging from 31.5 to 125 µM and 0.5 mg/mL (2.05 mM) was shown to have a positive effect against MERS-CoV and SARS-CoV, respectively, in Vero E6 cells [63,64]. Moreover, it reduced the viral RNA levels and infectious titers.…”
Section: Discussionmentioning
confidence: 96%